Optimizing Palm Oil Biodiesel Purity for a Cleaner Environment: Urea Complexation and RSM Approach - Zohera, Zohera; Helwani, Zuchra; Sunarno, Sunarno (Heca Sentra Analitika, 2025)
The performance and stability of biodiesel are strongly influenced by its fatty acid composition, particularly the balance between saturated (SFA) and unsaturated fatty acids (UFA). This study employed the urea inclusion compound (UIC) method to fractionate biodiesel and optimize conditions for obtaining a high-yield, high-quality saturated fraction (UCF). A central composite design (CCD) under response surface methodology (RSM) was used to evaluate the effects of urea-to-methanol ratio, crystallization temperature, and crystallization time on UCF and NUCF yields and iodine values. Experiments were conducted using a range of crystallization temperatures (18–22 °C), times (3–5 h), and urea-to-methanol ratios (1:1.5–1:2.5). The response variables were analyzed and optimized using desirability functions. The results showed that all three factors significantly influenced both the yield and iodine value of the fractions. The optimal condition, urea-to-methanol ratio of 1:1.73, temperature of 19.99 °C, and time of 5 h, yielded 81.59% UCF with an iodine value of 36.65 g I2/100 g, falling within the desired range for high-performance saturated biodiesel. In contrast, the NUCF fraction was minimized to 1.76% and enriched in PUFA. These findings demonstrate the potential of UIC-based fractionation for producing biodiesel with improved oxidative stability and combustion properties, aligning with international quality standards and contributing to more sustainable fuel formulations.